Designing Robust Fiduciary Markers for Indoor Localization - Kim, Gukhwan (University of Ottawa (Canada), 2010)
In this thesis, two fiduciary markers are newly designed as an alternate method for an indoor localization system. The main purpose of this work is to design more robust fiduciary markers than currently available ones in aspect of data restoration ability against data loss. In addition, achieving more accurate pose tracking performance is another goal of this work. Currently available fiduciary markers may not be ideal for indoor localization due to their lack of robustness against occlusions. Thus, proposed fiduciary markers must provide better performance under occlusions with respect to a marker detection rate. By adopting digital encoding/decoding techniques combined with using multiple sub-markers or PRMVS pattern, proposed ones achieved a better marker detection rate under partial occlusions. In addition, the experimental results show that proposed fiduciary markers provide more accurate camera pose measurement than other fiduciary markers.
Keywords: Engineering, Electronics and Electrical.